Comparative Study on the Efficiency of Mercury Removal From Wastewater Using Bacterial Cellulose Membranes and Their Oxidized Analogue - Suárez-Avendaño, D.; Martínez-Correa, E.; Cañas-Gutierrez, A.; Castro-Riascos, M.; Zuluaga-Gallego, R.; Gañán-Rojo, P.; Peresin, M.; Pereira, M.; Castro-Herazo, C. (Frontiers in Bioengineering and Biotechnology, 2022)
A comparative study was conducted on the efficiency of mercury removal using bacterial nanocellulose (BNC) membranes obtained from the fermentation of the microorganism Komagataeibacter medellinensis, in contrast with its oxidized analog obtained by modifying the bacterial nanocellulose membranes via oxidation with 2,2,6,6-Tetramethylpiperidine-1-oxyl. Both types of membranes (modified and unmodified) were characterized to identify variations in the Physico-chemical parameters after modification. FTIR spectra confirmed the chemical modification of cellulose in all reaction conditions by the presence of a new characteristic band at ∼1730 cm−1, corresponding to the new carboxylic groups produced by the oxidative process, and the decline of the band at ∼1,650 cm−1, corresponding to the hydroxyl groups of the C6 carbon. While the XRD profiles indicated that the percentage of BNC crystallinity decreased and the SEM images showed that the nanoribbon network was interrupted as the amount of oxidizing agent increased. The kinetics of mercury removal from both types of membrane was evaluated by calculating the concentration of mercury at different times and establishing a mathematical model to describe the kinetics of this process. The modified membranes improved significantly the adsorption process of the metal ion and it was found that the modification that results in the greatest adsorption efficiency was BNC-m 7.5 with a value of 92.97%. The results obtained suggest that the modification of the bacterial nanocellulose membranes by oxidation transcendentally improves the mercury removal capacity, outlining the modified membranes as an excellent material for mercury removal in wastewater.